Reclassification of Soil Type Maps for Evaluation of Forest Areas Using SMCA in Bogor Regency - Aditya Ramadhan; Adi Wibowo (Tunas Geografi, 2021)
AbstractSoil is a layer of the earth's surface that is formed due to the process of decomposition and weathering over a very long period. Soil is also included in the forest ecosystem as a place for vegetation to grow. In particular, the forest in Bogor Regency based on its function consists of protected forest, conservation forest, limited production forest, permanent production forest, and forest area as a buffer function. However, from year to year, the forest area in Bogor Regency has decreased due to land conversion. The purpose of this study is to examine the use of soil type variables on the suitability of forest area functions and provide a reference for processing soil types in terms of GIS utilization. The method used is a reclassification of raster data with Arcmap GIS 10.7 software. Based on the research results, there are five types of soil in the research area. After reclassification, the available soil classes based on their area are four categories, namely insensitive, moderately sensitive, less sensitive, and sensitive. Furthermore, the soil type variable is processed by weighting and scoring to determine the suitability of the function of the forest area and evaluated with the 2016-2036 Bogor Regency RTRW.Keywords: Reclassification, Soil Type, Suitability, Forest Area